Growth and Yield of Watermelon (Citrullus lanatus) in Plastic House in Response to White LED Supplementary Lighting - Somchai Glahan; Phonkrit Maniwara; Wasinee Chamchum; Somsak Kramchote; Patcharaporn Suwor (AGRIVITA, Journal of Agricultural Science, 2023)
Watermelon plants cultivar ‘Kinaree 457’ were grown in plastic house under natural daylight only (control) or with nightly LED supplementary lighting for 6 h (6:00 pm-12:00 pm) or 12 h (6:00 pm-6:00 am) starting from transplanting up to fruit harvest. Plant height, leaf chlorophyll content and fruit yield significantly increased in response to 6 h supplementary LED lighting. Fruit mass, size (length x width) and flesh thickness at 6 h LED treatment were about 2.3 kg, 19.3 ×15.7 cm, and 15.7 cm, respectively, while the fruit of control had 1.7 kg, 16.0 × 14.3 cm, and 13.8 cm, respectively. No significant treatment effect was obtained on peel thickness, flesh color L* and b* values, juice pH and total soluble solids. However, 6 h LED treatment resulted in lower reddening flesh (lower a* values), firmness and higher titratable acidity relative to the control, suggesting the need for improvement in cultural management. Furthermore, multivariate statistics of principal component analysis (PCA) performed on physico-chemical quality revealed the variations among watermelons from lighting and control treatments regardless of lighting hour.